Penyuluhan tentang Bahaya Penggunaan Narkotika, Psikotropika dan Obat-Obat Adiktif di MAS Yapensa Jenggot Kota Pekalongan - Hilda Prajayanti; Maslikhah Maslikhah (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2020)
Community service program with the topic "Counseling about the Dangers of Using Narcotics, Psychotropics and Addictive Drugs in MAS Yapensa, Jenggot-Pekalongan City" is intended to provide knowledge about the dangers of Narcotics in madrasa aliyah. The importance of providing education about the dangers of drug abuse early on is one of preventive steps. Drugs abuse now do not only attack the age of 20 years and over. Because starting from elementary students also must be aware of the dangers of drug trafficking. Its circulation is not only from a closed place but it can be from relationships, internet cafes and so on. Therefore, it can be said that in order to fortify himself from drugs abuse, the role of parents' attention is very important. It is completed by good religious knowledge and the role and education of schools. Moreover, environmental factors will greatly affect children. It is hoped that in the future this activity can be sustainable and encourage adolescents to be free from drugs. In addition, a pre-test and post-test were conducted to determine the level of knowledge before and after counseling. The results obtained are that there is a significant increase in students of MAS Yapensa, Jenggot-City Pekalongan after counseling about the Dangers of Drugs abuse.